Cohesive silicone gel implants with smooth, textured or polyurethane-coated surface to restore volume in eviscerated sockets - Abreu, Cristiano [UNESP]; Yamashita, Seizo [UNESP]; Galindo-Ferreiro, Alicia; Modolo, Marilia [UNESP]; Pellizzon, Claudia H. [UNESP]; Padovani, Carlos R. [UNESP]; Marques, Mariangela E. A. [UNESP]; Schellini, Silvana A. [UNESP] (Taylor & Francis Inc, 2018)
The purpose of this article is to evaluate the three different surface coating on cohesive silicone gel implants in eviscerated rabbit eye sockets. Forty-five albino rabbits underwent right eye evisceration and received hemisphere-shaped cohesive silicone gel implants with smooth (Group 1), textured (Group 2), or polyurethane-coated surface (Group 3) in the socket. The animals were euthanized at 7, 30, and 90 days postoperatively. Computed tomography of the orbits was performed prior to euthanasia. Subsequently, the orbital contents were removed and underwent histologic and morphometric examination. Data were statistically analyzed. There were no adverse effects throughout the study. The majority of implants in the Group 1 exhibited 180 degrees rotation. The Group 3 experienced an intense inflammatory reaction around the implant and implant deformation probably due to pseudocapsule contraction. Cohesive silicone gel implants had good integration into the scleral socket. Optimal results were obtained with cohesive silicone gel textured implants (Group 2). Smooth implants (Group 1) rotated significantly, whereas polyurethane (Group 3) coated implants precipitated an intense inflammatory reaction and were deformed postoperatively.
Keywords: Anophthalmic socket; cohesive silicone gel implant; experimental study; orbital implants; superficial texture